Ability of an oral formulation of afoxolaner to protect dogs from Borrelia burgdorferi infection transmitted by wild Ixodes scapularis ticks. (December 2016) - Baker, C.F.; McCall, J.W.; McCall, S.D.; Drag, M.D.; Mitchell, E.B.; Chester, S.T.; Larsen, D.
Highlights: Dogs were each infested with 50 wild-caught Ixodes scapularis ticks. PCR showed that 67% of the Ixodes scapularis ticks carried Borrelia burgdorferi . 28 Days after treatment of 10 dogs, NexGard killed Ixodes ticks before they could transmit Borrelia . The wild-caught Ixodes ticks transmitted Borrelia to 9 of the 10 control dogs. Abstract: A randomized, blinded, negative controlled study was conducted to determine whether treatment with afoxolaner (NexGard ®, Merial, Inc.) would prevent the transmission of Borrelia burgdorferi to dogs by wild caught Ixodes scapularis ticks. Twenty healthy dogs were randomly assigned to two groups of ten dogs each. Ten dogs were treated orally on Day 0 at a dose near the minimum recommended dose of afoxolaner of 2.5 mg/kg (actual doses 2.5–3.1 mg/kg) and ten control dogs were not treated. On Day 28, each dog was infested with approximately 50 adult unfed wild caught I. scapularis that had a 67% B. burgdorferi infection rate (determined by polymerase chain reaction). On Day 33, live ticks were counted and removed. No ticks were found on treated dogs while control dogs had an average of 21.4 ticks. To detect infection, the B. burgdorferi -specific C6 antibody SNAP ® 4Dx ® test (IDEXX) was performed on serum collected before infestation (all dogs seronegative on Days -6 and 27) and on Days 48, 63, 77 and 92. The ten treated dogs remained seronegative through the end of the study (Day 92), while nine out of the ten control dogs were infected, as demonstrated by their seroconversion to being positive for the presence of the B. burgdorferi -specific C6 antibody starting on Day 48. In this study, all dogs treated with NexGard ® 28 days prior to challenge with wild caught I. scapularis ticks were protected from B. burgdorferi infection, while nine out of the ten untreated control dogs were infected.